Sintesis dan Karakterisasi Selulosa Asetat (CA) - Souhoka, Fensia Analda; Latupeirissa, Jolantje (Indonesian Journal of Chemical Research, 2018)
Synthesis and characterization of cellulose acetate (CA) has been conducted. The cellulose used in this study was commecial a-cellulose in 92% content. All the CA products were analyzed by FTIR spectrometers. The determination of cellulose content was done using standart method of TAPPI T-203, while the determination of the degree of substitution (DS) was based on SNI 0444:2009 method. Conventional acetylation of cellulose was performed using gacial acetic acid, anhydride acetic acid, and sulfuric acid. The acetylation at 25 Â°C for 2.5 hours gave the DS of 1.482 and at 40 Â°C for 5 hours gave the higher DS 2.295.